The Effect of Short Selling on Market Reactions to Earnings Announcements - LASSER, DENNIS J.; WANG, XUE; ZHANG, YAN (Contemporary Accounting Research, 2010)
This paper examines the effect of the inherent demand implied by short interest by studying how stock price reactions to earnings announcements depend on the level of short interest. We find that, for extreme good and bad news events, the inherent demand increases stock prices around the earnings announcement date, with the effect being stronger for good news relative to bad news. Specifically, the initial market reaction to an extreme positive earnings surprise is larger for firms with high levels of short interest. On the other hand, for an extreme negative earnings surprise event, the initial market reaction is less negative for heavily shorted firms. Furthermore, we find that the post‐earnings‐announcement drift is smaller (larger) in magnitude for extreme positive (negative) earnings surprises for the heavily shorted firms.